Use and non-use values to explain farmers' motivation for the provision of animal welfare. (17th February 2021) - Owusu-Sekyere, Enoch; Hansson, Helena; Telezhenko, Evgenij
Abstract: This paper examines how differences in motivation in terms of use and non-use values affect the choice of animal welfare improvement practices. The application is focused on Swedish dairy farmers' preferences for different flooring systems' attributes. Using multiple indicators and multiple causes and hybrid latent class models, the findings demonstrate that dairy farmers who favour flooring solutions that enhance farm animal welfare are motivated by a complex set of both use values relating to internal and external pressures and non-use values linked to animal freedom, ethical codes of farmers and building business-to-customer relationships. The findings imply that measures to stimulate more uptake of animal welfare improvement practices can be better targeted by using insights into motivational constructs of farmers and by adopting policy communication that captures the whole breadth of use and non-use motivational constructs held by farmers.